Teaching of probability theory and combinatorics at secondary schools - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2004)
The topics of probability theory and combinatorics were brought into curricula of Lithuanian secondary schools ten years ago. The problems of teaching and actual situation of apprehension of concepts of probability theory and combinatorics are analyzed.
Keywords: probability theory; combinatorics; teaching; curricula; exams